Cardioprotective Signaling by Endothelin - Schorlemmer, Anita (2008)
The endothelin axis promotes survival signaling pathways in the heart, inviting the idea to use antagonists of endothelin signaling for the treatment of heart failure. Promising results from animal trials, however, failed to show beneficial effects in heart failure patients. Here we review the role of major signaling pathways in the heart that are involved in cell survival initiated by ET-1. These pathways include MAPK, PI3K/AKT,NF κB and calcineurin signaling. A better understanding of endothelin mediated signaling in cardiac cell survival may allow a re-evaluation of endothelin receptor antagonists in the treatment of heart failure.